Preparation and Characterization of Magnetite Fe3O4-Activated Carbon Composite as Adsorbent Cr(VI) Ion - Intan Lestari; Yonanda Ramadhanty; Leny Marlinda; Ngatijo Ngatijo (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2021)
Metal ion such as Cr(VI) is one toxic heave metal at the trace level, thus it is necessary to remove metal ion Cr(VI) ion environmental. The absorption of Cr(VI) ions was carried out using a Fe3O4 magnetite activated carbon composite. Activated carbon prepare from palm shells (Elaeis guinensis Jack) was composite with magnetite Fe3O4 by co-precipitation method. Magnetite Fe3O4-activated carbon composite is characterized by SEM, VSM and XRD. SEM image show that Fe3O4 a deposit on the surface of activated carbon. The degree of magnetization of Fe3O4 with VSM obtained 20.99 emu/g. The pattern of XRD diffractogram show that diffraction peak at 2θ which was 6.5495o; 30.1146o; 35.3581o; 43.063o; 57.1369o; 62.5918o. The spectra of FTIR show that functional groups exist in composites such as carboxyl, carbonyl and hydroxyl groups. Adsorption of Cr(VI) ion occurs at pH 5, contact time is 30 minutes and a maximum concentration of 200 mg/L Cr(VI) with a maximum adsorption capacity was 43.4 mg/g.